Analysis of Teacher Competence and Teacher Performance in the Border Area of Bengkayang District - Warneri Warneri (JETL (Journal of Education, Teaching and Learning), 2019)
This study aims to determine teacher competence and teacher performance in the learning process, and efforts made by the school so that teacher competence can be implemented optimally and know the maximum work results. The approach used in this study is qualitative. Data collection techniques used direct observation, direct communication, and communication indirectly with tools such as observation guidelines, questionnaires, and interview guidelines. Data analysis was inductive and the results of the study emphasize more meaning than generalization. Sources of the data and data in this study were teacher and headmasters as many as 40 people in the border area of Bengkayang District with Malaysia about the implementation of teacher competence and the result of teacher performance. The results showed that: (1) teacher competence in the border area of Bengkayang District, most of the teachers have implemented teacher competence well; (2) the performance of teachers in the border area of Bengkayang District, most of the teachers in implementing learning have been carried out actively and effectively and the assessment of learning also most have carried out learning evaluation to the maximum; (3) efforts made by the school to overcome teacher competence and teacher performance, in this case, are by carrying out planned and structured coaching and carried out continuously so that teachers can always carry out the mandate of the law and the awareness to improve the results that have not been maximized.